Fungal osteomylitus in diabetic patients and COVID-19 (Journal of Fatima Jinnah Medical University, 2022)
Background: COVID-19 pandemic has become a big medical problem worldwide. In this era, COVID-19 patients’ along with diabetes mellitus are at an increased risk of developing opportunistic infections. This study demonstrate association of COVID-19 infection in patients having uncontrolled diabetes with the fungal osteomyelitis.Subjects and methods: This prospective cross-sectional study was done at a Nishter Institute of Dentistry, Multan. Patients diagnosed with fungal osteomyelitis of jaw bones presented during April to December 2021 were included in this study. Data was collected from the patients regarding history of the disease, clinical diagnosis, imaging findings by plain radiographs and CT scans, histopathology. Association of disease process with diabetes and COVID-19 was analyzed in SPSS.Results: Between the period April 2021 to December 2021, 23 cases presented in Nishter Institute of Dentistry Multan with fungal osteomylitus were diagnosed clinically and fungal organism was identified by immunohistochemical studies by PAS and GMA stains. 22/23 (95.6%) patients were with uncontrolled diabetes mellitus and 18/23(78.2%) gave the history of Covid 19 infection 2 to 3 months before with moderate to severe symptoms.11/23 (47.8%) gave the history of treatment with systemic steroid. Age range was 38-72 years of age with mean age 53.26. 12/23(52.1%) were males and 11/23 (47.8%) were females. 17/23 (73.9%) patients presented with pain in jaws with exposed bone and 6/23(23%) complained of pain and loose teeth in arch. In 22/23 (95.6%) involved jaw was maxilla. In one patient associated medical condition was hepatitis C virus infection also with diabetes. 2 patients were cardiac and 3 were hypertensive along with diabetes. One patient was previously treated with radiotherapy of mandible due to alveolar cancer. Only one (0.04%) patient was non diabetic.Conclusion: There is increased incidence of fungal osteomyelitis of jaws mostly maxilla in diabetic and COVID-19 infected patients.
Keywords: Mucormycosis; Diabetics, COVID-19; Fungal osteomylitus of jaws; Maxillay osteomyelitis